Free 25-Hydroxyvitamin D: Impact of Vitamin D Binding Protein Assays on Racial-Genotypic Associations - Nielson, Carrie M.; Jones, Kerry S.; Chun, Rene F.; Jacobs, Jon M.; Wang, Ying; Hewison, Martin; Adams, John S.; Swanson, Christine M.; Lee, Christine G.; Vanderschueren, Dirk; Pauwels, Steven; Prentice, Ann; et al. (The journal of clinical endocrinology and metabolism, 2016)
Context:Total 25-hydroxyvitamin D (25OHD) is a marker of vitamin D status and is lower in African Americans than in whites. Whether this difference holds for free 25OHOD (f25OHD) is unclear, considering reported genetic-racial differences in vitamin D binding protein (DBP) used to calculate f25OHD.Objectives:Our objective was to assess racial-geographic differences in f25OHD and to understand inconsistencies in racial associations with DBP and calculated f25OHD.Design:This study used a cross-sectional design.Setting:The general community in the United States, United Kingdom, and The Gambia were included in this study.Participants:Men in Osteoporotic Fractures in Men and Medical Research Council studies (N = 1057) were included.Exposures:Total 25OHD concentration, race, and DBP (GC) genotype exposures were included.Outcome Measures:Directly measured f25OHD, DBP assessed by proteomics, monoclonal and polyclonal immunoassays, and calculated f25OHD were the outcome measures.Results:Total 25OHD correlated strongly with directly measured f25OHD (Spearman r = 0.84). Measured by monoclonal assay, mean DBP in African-ancestry subjects was approximately 50% lower than in whites, whereas DBP measured by polyclonal DBP antibodies or proteomic methods was not lower in African-ancestry. Calculated f25OHD (using polyclonal DBP assays) correlated strongly with directly measured f25OHD (r = 0.80–0.83). Free 25OHD, measured or calculated from polyclonal DBP assays, reflected total 25OHD concentration irrespective of race and was lower in African Americans than in US whites.Conclusions:Previously reported racial differences in DBP concentration are likely from monoclonal assay bias, as there was no racial difference in DBP concentration by other methods. This confirms the poor vitamin D status of many African-Americans and the utility of total 25OHD in assessing vitamin D in the general population.